Glycemic control and adherence to basal insulin therapy in Taiwanese patients with type 2 diabetes mellitus. Issue 6 (30th May 2016) - Chien, Ming‐Nan; Chen, Yen‐Ling; Hung, Yi‐Jen; Wang, Shu‐Yi; Lu, Wen‐Tsung; Chen, Chih‐Hung; Lin, Ching‐Ling; Huang, Tze‐Pao; Tsai, Ming‐Han; Tseng, Wei‐Kung; Wu, Ta‐Jen; Ho, Cheng; et al.
Abstract: Aims/Introduction: The aim of the present study was to assess the glycemic control, adherence and treatment satisfaction in a real‐world setting with basal insulin therapy in type 2 diabetes patients in Taiwan. Materials and Methods: This was a multicenter, prospective, observational registry. A total of 836 patients with type 2 diabetes taking oral antidiabetic drugs with glycated hemoglobin (HbA1c) >7% entered the study. Basal insulin was given for 24 weeks. All treatment choices and medical instructions were at the physician's discretion to reflect real‐life practice. Results: After 24‐week treatment, 11.7% of patients reached set HbA1c goals without severe hypoglycemia (primary effectiveness end‐point). HbA1c and fasting blood glucose were significantly decreased from (mean ± SD) 10.1 ± 1.9% to 8.7 ± 1.7% (−1.4 ± 2.1%, P < 0.0001) and from 230.6 ± 68.8 mg/dL to 159.1 ± 55.6 mg/dL (−67.4 ± 72.3 mg/dL, P < 0.0001), respectively. Patients received insulin therapy at a frequency of nearly one shot per day on average, whereas self‐monitoring of blood glucose was carried out approximately four times a week. Hypoglycemia was reported by 11.4% of patients, and only 0.7% of patients experienced severe hypoglycemia. Slight changes in weight (0.7 ± 2.4 kg) and a low incidence of adverse drug reactions (0.4%) were also noted. The score of 7‐point treatment satisfaction rated by patients was significantly improved by 1.9 ± 1.7 ( P < 0.0001). Conclusions: Basal insulin therapy was associated with a decrease in HbA1c and fasting blood glucose, and an improved treatment satisfaction. Most patients complied with physicians' instructions. The treatment was generally well tolerated by patients with type 2 diabetes, but findings pointed out the need to reinforce the early and appropriate uptitration to achieve treatment targets. Abstract : This observational study conducted in Taiwanese patients with type 2 diabetes showed that (i) Treatment of basal insulin therapy for 24 weeks significantly reduced HbA1c and FBG values, and was tolerated by patients without serious safety concern; (ii) Most of patients complied with physicians' instructions and were satisfied with the treatment; (iii) More meticulous titration may enable more patients to achieve treatment targets.